EVALUATION OF IMPLEMENTATION OF INCLUSION EDUCATION PROGRAMS IN MADRASAH IBTIDAIYAH BADRUSSALAM SURABAYA - Evi Sopandi; Khasanah Khasanah (Akademika : Jurnal Teknologi Pendidikan, 2020)
This study aims to evaluate the inclusive education program at Madrasah Ibtidaiyah (MI) Badrussalam Surabaya. The education program aims to improve human resource competencies in increasing abilities. The evaluation model used in this study is the CIPP model (context, input, process, and product) of the qualitative research approach model introduced by Stufflebeam. The results showed that the education program at MI Badrussalam Surabaya had run well in accordance with the education program that had been prepared. However, in the implementation of inclusive education in MI Badrussalam, there are still some deficiencies both in the fields of funding, facilities and infrastructure as well as on the Welfare of mentors and special teachers (GP / K).